Experimental and kinetic comparative study on ignition characteristics of 1-pentene and n-pentane. (15th May 2016) - Cheng, Yu; Hu, Erjiang; Deng, Fuquan; Yang, Feiyu; Zhang, Yingjia; Tang, Chenglong; Huang, Zuohua
Highlights: Ignition delay times of 1-butene and n -pentane were measured in a shock tube. NG model, JetSurF2.0 model and Touchard model were validated. NG model was updated to form Aramco-NG model. Ignition delay times of 1-pentene and n -pentane were compared and the crossover of ignition delay times were explained. Abstract: Ignition delay times of 1-pentene and n -pentane were measured using a shock tube at pressures from 0.12 MPa to 1.0 MPa, at equivalence ratios from 0.5 to 2.0 with 0.5% and 1.0% fuel concentrations, in the temperature range of 1040–1880 K. Correlations of 1-pentene and n -pentane ignition delay times were deduced from the experimental data using a multiple linear regression. A NG model, JetSurF2.0 model and Touchard model were used to simulate the experiments but the performance was not good for all data. The C1–C4 sub-model of the NG model was updated using Aramco Mech 1.3, forming the Aramco-NG model, which conformed closely to the experiments. A crossover of the ignition delay times of 1-pentene and n -pentane can be observed in the correlations and calculations as well as in the experimental data. The shorter ignition delay times of 1-pentene in the relative low temperature region can be explained by the abundant H atom producing channels and the higher rate constant of the unimolecular decomposition reaction in this region. In the relative high temperature region, the higher amount of allyl radical formed through the breakage of the Cγ Cδ bond and lower concentration of oxygen may contribute to the longer ignition delay times for 1-pentene compared with n -pentane.